The Judge’s Role in the Effectiveness of Anti-Corruption Enforcement in Indonesia: A Juridical Analysis - Behuku, Jitro Gianfranco; Kusuma, Jevine Ilonesia; Chasanah, Nabila Uswatun; Sugianto, Fajar; Indradewi, Astrid Athina (SIGn Jurnal Hukum, 2025)
The effectiveness of anti-corruption law enforcement in Indonesia is facing a severe legitimacy crisis. This condition is characterized by a paradox between a robust legal framework on paper and its inadequate implementation in practice, thereby eroding public trust. This research aims to critically analyze the central role of judges in determining this effectiveness, with an analytical focus on the problematic interpretation of legal norms and the systemic challenges that impede judicial performance. Through a normative legal approach fortified by a case study, this research employs qualitative content analysis to dissect the legal reasoning in two key 2024 decisions from the Corruption Crimes Court. The findings reveal a diametrically different legal treatment of defendants. On one hand, the court was capable of convicting an individual defendant (a rogue judge) through a procedural application of the law. On the other hand, the court acquitted five large corporations of all legal charges in a corruption case that resulted in significant state economic losses. This acquittal was based on the legalistic argument that the proven act did not constitute a criminal offense. This dualism confirms that law enforcement effectiveness remains sporadic, undermined by a disparity in the professional capacity of judges to interpret the element of “unlawful act,” particularly in complex corporate crimes. It is concluded that without systemic judicial reform to standardize legal interpretation and strengthen accountability, anti-corruption law enforcement will remain blunted when confronting powerful economic actors.